APPRAISAL OF PRIVATE SECTOR INVESTMENTS IN ECOTOURISM INDUSTRY IN OGUN STATE, NIGERIA (2013)
Ecotourism is a capital intensive industry that requires private sector participation to complement government’s efforts in its development. Information on private investments contributions to Ogun state ecotourism industries is scanty. This study was therefore carried out to appraise private sector investments in ecotourism in Ogun state with the view to ascertaining economic viability of investing in the industry. The twenty-eight registered private ecotourism firms (botanical garden, resort centre, zoological garden, wildlife souvenir and water recreation/natural pool) in Ogun state were enumerated. Purposive sampling was used for the selection of 65 hospitality firms (hotel, catering services and motel) within five to 10km radius of the firms. Primary data were obtained from relevant governmental and non-governmental agencies, community based and labour organisations using structured questionnaire on demography of investors (proprietors), existing government policies on tourism investments, factors militating against investments and promotions of private investments in ecotourism. Cost-Benefit Ratio (CBR), Net Present Value (NPV), Internal Rate of Return (IRR) and Rate of Return on Investments (RRI) were determined to assess the economic viability of investing in ecotourism site. Data were analysed using descriptive statistics and chi square at p = 0.05. Private investments in ecotourism firms were in resort centres (39.2%), botanical gardens (17.4%), water recreation (26.1%), wildlife souvenir (13.1%) and zoological gardens (4.2%). Meanwhile, 36.9% of the private investors have been in the business for more than 10 years. Sources of capital for initial investments in ecotourism industry were bank loan (30.3%), personal savings (43.4%), government assisted (3.9%) and informal loans (22.4%). The patronage patterns of ecotourism sites in Ogun state were weekdays (8.6%), weekends (26.1%), public holiday (57.1%) and vacation/leave (8.2%). Initial total investments cost was between N 3,155,000 and N25, 012,000. The least average price charged visitor/tourist for services rendered by the firm were N200. Furthermore, 92.1% of investors were of the views that budgetary allocations to ecotourism industry are insufficient. However, 98.7% of the investors in ecotourism regarded electricity supply as epileptic whereas 82.9% considered the present condition of road facilities and network in Ogun state as bad. There was significant relationship between private investments and operational registration of business with government (χ² = 76.89), incentive for investors (χ² = 39.77) and marketing strategies/sales promotion (χ² = 28.37) in ecotourism industry. Private investments in ecotourism site in Ogun state had cost-benefit ratios between 1.14 and 1.80. The NPV was positive at 25.0% and 35.0% interest rates. The IRR was above the interest rates with minimum and maximum values of 57.2% and 137.4% respectively. The RRI was positive with highest return of 79.7% on interest rate of 25% except for one firm which had 23.6% returns. Existing private investments in ecotourism sites in Ogun state were economically viable but in a small scale. It is important that the state government aggressively improves on infrastructural development and budgetary allocations to ecotourism for rapid development of the industry.